2016
DOI: 10.1371/journal.pone.0152752
|View full text |Cite|
|
Sign up to set email alerts
|

Feeling of Pleasure to High-Intensity Interval Exercise Is Dependent of the Number of Work Bouts and Physical Activity Status

Abstract: ObjectivesTo examine the affective responses during a single bout of a low-volume HIIE in active and insufficiently active men.Materials and methodsFifty-eight men (aged 25.3 ± 3.6 years) volunteered to participate in this study: i) active (n = 29) and ii) insufficiently active (n = 29). Each subject undertook i) initial screening and physical evaluation, ii) maximal exercise test, and iii) a single bout of a low-volume HIIE. The HIIE protocol consisted of 10 x 60s work bouts at 90% of maximal treadmill veloci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
74
4
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(89 citation statements)
references
References 55 publications
10
74
4
1
Order By: Relevance
“…In addition, recent studies have suggested that sedentary individuals report pleasant feelings during the first three of four bouts of low‐volume HIT (Frazão et al . ), but importantly enjoyment of HIT increases as participants progress through a training programme (Heisz et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, recent studies have suggested that sedentary individuals report pleasant feelings during the first three of four bouts of low‐volume HIT (Frazão et al . ), but importantly enjoyment of HIT increases as participants progress through a training programme (Heisz et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…This may (Frazão et al, 2016;Saanijoki et al, 2015), or may not (Freese et al, 2014;Jung et al, 2014) be the case for HIT protocols that rely on many (4-10) longer (30-60 s) sprints, but the ratings of perceived exertion in response to two 20-s sprints as used in the REHIT protocol in the present study appear to be manageable, and the majority of participants (12 out of 16) stated a preference for performing REHIT rather than the walking intervention based on current physical activity recommendations. There is therefore an urgent need to perform further studies examining the efficacy, acceptability, and longer-term adherence to REHIT as a practical 'real-life' intervention.…”
Section: Discussionmentioning
confidence: 99%
“…However, due to the required recovery periods in between high-intensity bouts, most available HIT protocols are not as time-efficient as often claimed (Gillen & Gibala, 2014), and even in submaximal HIT protocols the high number of high-intensity bouts per training session results in high perceived exertion (Little et al, 2011). Moreover, repeating sprints more than ~4 times has a negative impact on the affective response to HIT (Frazão et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a drawback of the use of SIT 256 as a public health intervention is the potential for high associated perceived exertion and 257 negative affective responses (8,21). In this light it is important to point out that the number of 258 sprint repetitions has been shown to negatively affect both of these parameters (19,44). 259…”
Section: Matched Energy Expenditure (Studies Of a Targeted Risk Reducmentioning
confidence: 99%